2022
DOI: 10.3390/nu14153189
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fibre and Organic Acids in Kiwifruit Suppress Glycaemic Response Equally by Delaying Absorption—A Randomised Crossover Human Trial with Parallel Analysis of 13C-Acetate Uptake

Abstract: Non-sugar components of kiwifruit reduce the amplitude of the glycaemic response to co-consumed cereal starch. We determined the relative contribution of different non-sugar kiwifruit components to this anti-glycaemic effect. Healthy participants (n = 9) ingested equal carbohydrate meals containing 20 g starch as wheat biscuit (WB, 30 g), and the sugar equivalent of two kiwifruit (KFsug, 20.4 g), either intrinsic or added as glucose, fructose and sucrose (2:2:1). The meals were WB+KFsug (control, no non-sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A limitation of the present study was that the resources available limited the number of secondary outcomes, such as hormonal changes, that were measured. However, in a previous study on the interaction of WB and KF, we showed that the glycaemic response to both WB and KF, and combinations of the two, were followed very closely by insulin [ 4 ], with a correlation of R = 0.98. Further research using fewer food combinations and larger numbers of participants than in the present study should measure changes in various hormones governing glucose homeostasis and appetite, as objective physiological correlates to support the clear changes in both glycaemic response and appetite observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A limitation of the present study was that the resources available limited the number of secondary outcomes, such as hormonal changes, that were measured. However, in a previous study on the interaction of WB and KF, we showed that the glycaemic response to both WB and KF, and combinations of the two, were followed very closely by insulin [ 4 ], with a correlation of R = 0.98. Further research using fewer food combinations and larger numbers of participants than in the present study should measure changes in various hormones governing glucose homeostasis and appetite, as objective physiological correlates to support the clear changes in both glycaemic response and appetite observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Kiwifruit also contain a high concentration of organic acids with a low pH (about pH 3.4) and a high buffering capacity. In vivo studies showed that both fibre and organic acids in kiwifruit contributed to a reduced glycaemic response to co-consumed WB [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Components that slow the absorption of sugars so that sugar disposal processes for removal of fructose and glucose from the blood can match blood sugar loading, preventing high and/or prolonged blood sugar concentrations. Cell wall remnants (dietary fibre), organic acids, and phenolic compounds may all slow glucose absorption from the gut [17].…”
mentioning
confidence: 99%